Kant's place in the History of Philosophy - Plečkaitis, Romanas (Problemos, 1974)
The seminar devoted to the 250th anniversary of I. Kant’s birth was held on the 17th of April 1974 in Vilnius University. Some of the addresses read at the seminar are published in this issue. R. Plečkaitis speaks on I. Kant’s place in the history of philosophy. Problems of genuine importance are major subjects of Kantian philosophy.